A New Avenue to One-Pot Four-Component Synthesis of Spiro[Indoline-3,4'-Quinoline] Derivative Using DABCO As A Green Catalyst - Maury S.K.; Singh S. (My University, 2025)
A simple, efficient, and green, one-pot four-component synthesis of spiro [Indoline-3,4'-quinoline] has been developed from isatin, ethyl cyanoacetate, dimedone, and aniline using green catalyst DABCO and green solvent ethanol. The current method generates good to exceptional yields in a short reaction time and provides a broad substrate scope. This method also works for gram-scale reactions. © 2022 Georg Thieme Verlag. All rights reserved.